4 - 4x = -12
Subtract 4 from both sides: -4x = -16
Multiply both sides by -1: 4x = 16
Divide both sides by 4: x = 4
In 6x + 4 = 12, x = 4/3
It is: (3x+4)(2x-3) when factored
-6x-4-8 = -6x -12
It is: 12-12 = 0
6/12 - 4/16 is equal to 1/2 - 1/4 and that is equal to 1/4
In 6x + 4 = 12, x = 4/3
12
It is: (3x+4)(2x-3) when factored
12/3 minus 3/4 is 3 1/4 or 3.25
4/7 minus 5/12 = 13/84
-6x-4-8 = -6x -12
It is: 12-12 = 0
6/12 - 4/16 is equal to 1/2 - 1/4 and that is equal to 1/4
4
X is less than or equal to 4.
(x-2)(x-4) = 0 x = 2 or x = 4
6(x - 4)